ACCRUAL-BASED GOVERNMENT FINANCIAL REPORTING INFORMATION SYSTEM: ACCEPTANCE MODEL FROM AN INDONESIAN MUNICIPAL GOVERNMENT - Hendrawan Santosa Putra, Abdul Rohman, Tri Jatmiko Wahyu Probowo, Wahyu Agus Winarno (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The implementation of a full accrual base in the Indonesian government has a significant impact on changes in the government accounting system. These changes in accounting recognition base have a substantial effect on the readiness of human resources and the accounting reporting information system technology. This research aims to test and analyze user acceptance on government accrual reporting information system technology. This study uses a survey of financial administrators who have been interacting with the new financial reporting system in 33 work units in an Indonesian municipal jurisdiction. The sampling technique uses random cluster sampling, and the hypothesis testing uses structural equation modeling. All variables using the technology acceptance model showed significant results, except for the effect of computer self-efficacy on perceived ease of use. These results showed that TAM could predict the acceptance of an accounting information system in government accrual accounting.